2002
DOI: 10.1190/1.1527099
|View full text |Cite
|
Sign up to set email alerts
|

Estimating shallow shear velocities with marine multicomponent seismic data

Abstract: Accurate models of shear velocities in the shallow subsurface 300 m depth beneath the sea oor would help to focus images of structural discontinuities constructed, for example, with P to S converted phases in marine environments. Although multi-component marine seismic data hold a wealth of information about shear velocities from the sea oor to depths of hundreds of meters, this information remains largely unexploited in oil and gas exploration o shore. We present a method, called the Multi-Wave Inversion MWI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 51 publications
(34 reference statements)
2
49
1
Order By: Relevance
“…Nolet and Dorman (1996) used waveform fitting to show that starting from 30 m/s, S-wave velocity increases with a gradient of 2.8 m/s per meter over the first 150 m of sediment. Ritzwoller and Levshin (2002) constructed a reliable S-wave model to a depth of 200 m. In other studies, Forbriger (2003a, b) observed a remarkably good resolution of S-wave velocity in 6 and 16 m down to the bedrock, respectively. With their promising approach, Bohlen et al (2004) are able to apply to a dense net of profiles to derive 2-D models of surface S-wave velocity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nolet and Dorman (1996) used waveform fitting to show that starting from 30 m/s, S-wave velocity increases with a gradient of 2.8 m/s per meter over the first 150 m of sediment. Ritzwoller and Levshin (2002) constructed a reliable S-wave model to a depth of 200 m. In other studies, Forbriger (2003a, b) observed a remarkably good resolution of S-wave velocity in 6 and 16 m down to the bedrock, respectively. With their promising approach, Bohlen et al (2004) are able to apply to a dense net of profiles to derive 2-D models of surface S-wave velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Nolet and Dorman (1996) adapted method of non-linear waveform fitting to accommodate multidimensional model and applied it to invert several record sections of Scholte waves. Ritzwoller and Levshin (2002) presented multiwave inversion method which can adapt to a wide variety of information in marine seismic data. Forbriger (2003a, b) described his new approach on the inversion of shallow-seismic wavefields.…”
Section: Introductionmentioning
confidence: 99%
“…up to 300 m in Ritzwoller & Levshin (2002) and for the upper tens of metres in Nguyen et al (2009)). The success of these techniques is directly related to the distance of the active source to the seafloor.…”
Section: Previous Studies Of Oceanic S-wave Velocitymentioning
confidence: 99%
“…The success of these techniques is directly related to the distance of the active source to the seafloor. The closer the source is located to the seafloor the more acoustic energy can be converted into S-wave energy (Ritzwoller & Levshin 2002). The inversion of these active data results in high resolution S-wave velocity models, but it is limited to the upper hundreds of metres beneath the seafloor.…”
Section: Previous Studies Of Oceanic S-wave Velocitymentioning
confidence: 99%
“…Another popular approach is to invert the dispersion curves of the Scholte wave ͑e.g., Caiti et al, 1994;Ritzwoller and Levshin, 2002;Park et al, 2005͒. These P-SV polarized waves, traveling along the water-bottom interface, are highly sensitive to the shear-wave velocity.…”
Section: Introductionmentioning
confidence: 99%